Pengelompokan Data Rekam Medis pada Pasien Penyakit dalam Untuk Meningkatkan Manajemen Informasi Kesehatan Berdasarkan Wilayah Kota Binjai Menggunakan Algoritma Clustering K- Means : (Studi Kasus: Artha Medika Binjai) - Desiska Natalia Br. Purba; Marto Sihombing; Indah Ambarita (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The history of disease in patients is generally recorded in medical record data in every hospital as well as at Artha Medika Hospital which is a health institution that was established in 2012 in the city of Binjai also has a very large amount of medical record data. However, in using the information management system owned by Artha Medika Hospital, there are weaknesses and it is still limited in managing medical record data in the hospital which is used in making reports to the head of the leadership. Therefore, a system is needed that can assist the hospital in improving health information management to be faster in managing data by approaching using data mining techniques with the k-means method. So that in finding new information based on medical record data of internal medicine patients can be used in the decision-making process by hospital management to be right on target so that it can produce 3 groups of data consisting of Age, Type of disease and Region. From testing on cluster 3, it can be seen that the results of the age group (X), type of disease (Y), region (Z) the amount of data owned is 645 cluster 3 data centred on the centroid of the information of the number of patient medical records data, namely age is 44-52 years, with the type of disease is chronic kidney disease and the region is South Binjai.